Pre-Service Program for Physical Education Teacher Education: Research Trends - Ilmawati, Hilda; Juliantine, Tite; Suherman, Adang; Fahri, Achmad Syakur; Agus, Herdiansyah (TEGAR: Journal of Teaching Physical Education in Elementary School, 2024)
The role of a physical education teacher is a long-term career, and efforts to improve the competence of physical education teachers must be the concern of several parties, such as universities, training institutions, and even the Ministry of Education. This concerns the indicators that should be included in the various training programs for prospective physical education teachers. Currently, there is no standardization of the quality of a physical education teacher who is qualified to teach at different levels of education. Several studies have discussed professional development for physical education teachers. However, there has not been much research on pre-service programs for physical education teachers. The purpose of this study is to determine the trend of research on pre-service physical education teacher education (PETE) in different countries from 2014 to 2023. Visualization was done using VOSviewer. The research was conducted with a bibliometric study. The results of bibliometric analysis showed that the most research related to this topic was conducted in the United States with 79 research publications and 1172 citations. The findings provide insight for researchers to identify the components that need to be provided in the pre-service program for prospective physical education teachers in Indonesia.